Surgical treatment of patients with spinal cord injury, using tightening clamps with shape-memory effect - Salkov, Mykola (Ukrainian Neurosurgical Journal, 2014)
Introduction. There is an alternative to transpedicular stabilization, rigid fixation with clamps over the arcs or spine or vertebrae, occipitospondylodesis screw system — tightening clamps with shape-memory effect, made of nitinol. Materials and methods. In 2013, 15 decompressive-stabilizing operations using tightening clamps memory were performed. Occipitospondylodesis on the cervical spine was performed in 1 case, sub-axial fixation — in 6, combined approach was used in 2 patients. Results. Fixation took 15–20 min. System instability was not revealed in postoperative period. Radiation exposure of the patients’ body was reduced due to limiting the use of electronic-optical converter. Conclusions. 1. Use of tightening clamps with shape-memory effect reduces surgery lasting, surgical trauma, and blood loss. 2. The system is easy to install and reliable in fixation. 3. The method reduces risk of intra- and postoperative complications (liquorrhea, injuries of vertebral arteries and major blood vessels, neurological disorders). 4. Intraoperative radiation exposure of the patients’ body is insignificant.